Physical activity on prescription (PAP): self-reported physical activity and quality of life in a Swedish primary care population, 2-year follow-up - Lars Rödjer; Ingibjörg H. Jonsdottir; Mats Börjesson (Scandinavian Journal of Primary Health Care, 2016)
Objective: To study the self-reported level of physical activity (PA) and quality of life (QOL) in patients receiving physical activity on prescription (PAP) for up to 24 months. Design: Observational study conducted in a regular healthcare setting. Setting: A primary care population in Sweden receiving physical activity on prescription as part of regular care was studied alongside a reference group. Subjects: The group comprised 146 patients receiving PAP at two different primary care locations (n = 96 and 50, respectively). The reference group comprised 58 patients recruited from two different primary care centres in the same region. Main outcome measurements: We used two self-report questionnaires – the four-level Saltin-Grimby Physical Activity Level Scale (SGPALS) to assess physical activity, and SF-36 to assess QOL. Results: A significant increase in the PA level was found at six and 12 months following PAP, with an ongoing non-significant trend at 24 months (p = .09). A clear improvement in QOL was seen during the period. At 24 months, significant and clinically relevant improvements in QOL persisted in four out of eight sub-scale scores (Physical Role Limitation, Bodily Pain, General Health,Vitality) and in one out of two summary scores (Physical Component Summary). Conclusion: Patients receiving PAP showed an increased level of self-reported PA at six and 12 months and improved QOL for up to 24 months in several domains. The Swedish PAP method seems to be a feasible method for bringing about changes in physical activity in different patient populations in regular primary healthcare. While increased physical activity (PA) is shown to improve health, the implementation of methods designed to increase activity is still being developed.Key points The present study confirms that the Swedish physical activity on prescription (PAP) method increases the self-reported level of PA in the primary care setting at six and 12 months. Furthermore, this study shows that PAP recipients report a clinically relevant long-term improvement in quality of life, persisting for two years post-prescription, thus extending earlier findings. These findings have clinical implications for the implementation of PAP in healthcare.